Altered neutrophil responses to dengue virus serotype three: delayed apoptosis is regulated by stabilisation of Mcl-1 - Kamsom, Chatcharin; Edwards, Steven W.; Thaosing, Jiraphon; Papalee, Saitharn; Pientong, Chamsai; Kurosu, Takeshi; Phanthanawiboon, Supranee (Scientific reports, 2024)
Dengue is a global health concern, and the host-viral interactions that regulate disease severity are largely unknown. Detrimental effects of neutrophils in this disease have been reported, but the precise mechanisms and functional properties of dengue-activated neutrophils are not fully characterised. Here, we measured the effects of dengue virus serotype 3 (DV3) on neutrophil lifespan and functions. We show that DV3 extends neutrophil survival with a significant proportion of cells surviving for 72 h post-incubation. These effects on neutrophil survival were greater than those observed by adding GM-CSF and TNF-α alone, but these cytokines enhanced survival induced by the virus. Enhanced reactive oxygen species (ROS) generation was observed following incubation with DV3 activation and this ROS production was enhanced by co-incubation with priming agents. In addition, DV triggered the enhanced IL-8 expression by the majority of neutrophils and a low percentage of cells were activated to express MCP-1 (CCL2). A low number of neutrophils showed increased co-expression of the migratory markers, CCR7 and CXCR4 which could promote their migration towards lymph nodes. DV3 significantly upregulated the BCL-XL gene at 3, 12, and 24 h, and the Mcl-1 gene at 12 h, following treatment. We also show that DV3 induces the Mcl-1 protein stabilization similar to GM-CSF. This report sheds new light on the mechanisms by which neutrophils may contribute to the pathology of dengue disease via delayed apoptosis and generation of pro-inflammatory molecules, and raises the possibility that dengue-activated neutrophils may play a role in activating cells of adaptive immunity.